199 Characterizing Digestion Traits of Corn Bran Products from Corn Wet Milling. (12th April 2022) - Xiong, Jiehua; Suntara, Chanon; Sjostrand, Rebecca; Spore, Tyler; Youngers, Maggie; Stock, Rick; Erickson, Galen E; MacDonald, Jim C
Abstract: Evaluation of new bran products are necessary for continual improvement of wet milling feeds used by the cattle industry. The objective of this study was to evaluate 3 novel corn bran products from Cargill Corn Milling on rumen fermentation and nutrient digestion in beef cattle. Eight ruminally fistulated beef steers were utilized in a 4×4 replicated Latin Square design with 4 dietary treatments and 4 periods (21 d in length for each period with 14 d of adaptation and 7 d of collection). Four treatment diets were bran products (Bran A/B/C) included at 70% of diet dry matter (DM) with 25% steam flaked corn (SFC), and an internal control (SFC control) diet consisted of 70% SFC and 25% Sweet Bran, with 5% wheat straw in all 4 diets. The SFC control exhibited the greatest DM, organic matter (OM) and starch digestibility ( P ≤ 0.06), and the least neutral detergent fiber (NDF) digestibility ( P < 0.01). When 3 bran products each included at 70%, there was no difference in DM or OM intake and digestibility. Starch and NDF digestibility were greatest ( P < 0.01) for bran A fed steers, least for bran C with bran B intermediate. Bran products had minimal effect on energy digestibility, ruminal pH, rumination activity and jugular vein blood parameters. Total ruminal VFAs concentration was greatest ( P = 0.04) for SFC control, with no difference among bran A, B and C fed steers. Acetate: Propionate ratio was least ( P < 0.01) for SFC control fed steers, greatest for bran A with bran B and C being intermediate. Digestion trait differences existed among different corn bran products, of which feeding bran A resulted in better digestion of starch and NDF, and greater starch content of bran B and C resulted in greater ruminal propionate production.